Effective bisquaternary reactivators of tabun-inhibited AChE - Kuca, Kamil; Cabal, Jiri; Musilek, Kamil; Jun, Daniel; Bajgar, Jiri (Journal of applied toxicology, 2005)
Two cholinesterase reactivators (K074 and K075) were synthesized and their reactivation efficacy against tabun-inhibited acetylcholinesterase of the rat brain was tested in vitro. Comparing this efficacy showed that commonly used oximes (pralidoxim, obidoxime and HI-6) were practically without reactivation potency. On the other hand, oximes K074, K075 and trimedoxime were satisfactorily effective. Moreover, K-oximes reactivated tabun-inhibited AChE at lower concentration (10(-4) and 10(-3) m) in comparison with trimedoxime (10(-3) and 10(-2) m). Thus, K-oximes can be considered as the most effective reactivators of tabun-inhibited AChE at present.
Keywords: Cholinesterase Inhibitors; Rats, Wistar; Structure-Activity Relationship; Brain; techniky in vitro; vztah mezi dávkou a účinkem léčiva; Pyrimidines; Oximes; potkani Wistar; acetylcholinesterasa; Cholinesterase Reactivators; Pyridinium Compounds; vztahy mezi strukturou a aktivitou; butany; krysa rodu Rattus; organofosfáty; kinetika; Animals; pyridinové sloučeniny; ženské pohlaví; zvířata; pyrimidiny; Rats; reaktivátory cholinesterasy; mozek; oximy; Female; Acetylcholinesterase; cholinesterasové inhibitory; Dose-Response Relationship, Drug; Kinetics; Organophosphates; In Vitro Techniques; Butanes